2019
DOI: 10.1017/s204017441900031x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding duration is associated with offspring’s adherence to prudent dietary pattern in adulthood: results from the Nutritionist’s Health Study

Abstract: Little is known about the long-term effect of breastfeeding on dietary habits. We examined the association between breastfeeding duration and adherence to current dietary patterns of young women. This was a cross-sectional analysis of 587 healthy women aged ≤45 years, undergraduates or nutrition graduates. Maternal characteristics and breastfeeding duration [<6; 6–<12; ≥12 months (reference)] were recalled. Diet was assessed using a food frequency questionnaire and patterns were identified using factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 59 publications
(77 reference statements)
2
23
2
Order By: Relevance
“…The third mechanism refers to common environmental factors, transmitted from mother to offspring, such as dietary habits (9,32) . Our previous study (12) showed that daughters of overweight mothers had lower chance to adhere to a prudent diet, characterised by healthy foods such as fruits, vegetables and whole grains, and higher chance to adhere to a processed diet, composed of high energy density foods, such as fast foods, sweets and fried food, which could favour body fat accumulation (35) .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
See 2 more Smart Citations
“…The third mechanism refers to common environmental factors, transmitted from mother to offspring, such as dietary habits (9,32) . Our previous study (12) showed that daughters of overweight mothers had lower chance to adhere to a prudent diet, characterised by healthy foods such as fruits, vegetables and whole grains, and higher chance to adhere to a processed diet, composed of high energy density foods, such as fast foods, sweets and fried food, which could favour body fat accumulation (35) .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Genetic components could partly explain this association (9) , but it is known that epigenetic mechanisms, through metabolic programming during the first 1000 d of life, play an important role on this issue (10,11) . Maternal lifestyle, mainly related to dietary intake habits, may influence offspring behaviours and risk for outcomes (9,12) . In this context, our group found that maternal pre-pregnancy BMI was associated with offspring adherence to a processed and prudent dietary pattern in adulthood (12) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants of both sexes answered online structured questionnaires regarding sociodemographic data, family history, early life events, lifestyle, current diet, and clinical data. 16,17 Further, a convenience sample of the first 200 healthy participants (extra 10% to compensate losses) was invited to visit the health care center of the School of Public Health of the University of São Paulo for clinical examination, biological samples collections, and to undergo muscle performance tests and DXA.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…Eshriqui et al 4 asked a group of healthy premenopausal women to recall their duration of breastfeeding and related this to their ability to adhere to a dietary pattern. Interestingly, those women who reported a longer duration of breastfeeding were more likely to adhere to a prudent dietary habit.…”
mentioning
confidence: 99%